The efficacy of antithrombin administration in the acute phase of burn injury - Lavrentieva, Athina; Kontakiotis, Theodore; Bitzani, Militsa; Parlapani, Aggeliki; Thomareis, Olympia; Scourtis, Harisios; Tsotsolis, Nicolaos; Lazaridis, Lambis; Giala, Maria-Amalia (Thrombosis and Haemostasis, 2008)
Severe burn injury is characterized by the activation of coagulation, decreased fibrinolytic activity and decreased natural anticoagulant activity. The aim of our study was to investigate the effect of antithrombin (AT) administration on coagulation status and on organ function in the early post-burn period. Thirty-one patients were admitted to the burn intensive care unit and were then randomised into two groups (AT- treated and non-AT-treated) for four consecutive days after thermal injury. The clinical data, coagulation and fibrinolysis parameters were compared and the adverse effects were monitored. Significant differences in the time course of coagulation markers (thrombin/AT complexes, tissue plasminogen activator, D-dimer) were observed between AT-treated and non-AT treated groups. According to the International Society onThrombosis and Haemostasis criteria, disseminated intravascular coagulation (DIC) diagnosis was made in 28 of 31 patients. The presence of overt DIC was associated with mortality (p<0.001).The Sequential Organ Failure As-sessment (SOFA) score time trend differed significantly between the two investigation groups (decreased in the treated group and did not change in the non-AT-treated group). AT-treated patients had an absolute reduction in a 28-day mortality of 25% as compared to the non-AT-treated group (p=0.004). No treatment related side effects were observed. Treatment withAT seems to affect the coagulation status and reduce multiple organ failure incidence and mortality in the early post-burn period.
Keywords: Antithrombin; burn injury; coagulation markers; disseminated in-travascular coagulation; sequential organ failure assessment score